(untitled) (Perioperaciina Medicina, 2019)
Psychomotor excitation, delayed recovery of consciousness after general anesthesia – well-known conditions. But only in the literature of Germany, it was first isolated in a separate central anticholinergic syndrome (CAS). This article discusses the main aspects and symptoms that will help to differentiate this syndrome with other conditions, and the methods for relief of this state.